Enhancing Undergraduate Students' Competency in Quantitative Data Processing for Academic Writing Through a Statisty.app-Based Workshop - Muhammad Ammar Naufal; Mansyur Mansyur; Muhammad Saddang; Hisyam Ihsan; Ahmad Zaki (Journal of Community Services and Development, 2026)
This community service activity aimed to enhance the quantitative data processing competency of undergraduate students through a Statisty.app-based workshop held at Universitas Negeri Makassar (UNM) on April 25, 2026. Statisty.app is a free, web-based statistical analysis platform requiring no installation. A total of 53 students participated in the pre-test and 48 in the post-test, predominantly from the first and second semester (92.5%) and with no prior training in data analysis (94.3%). The workshop covered six sessions: introduction to quantitative data, Statisty.app orientation, data preparation, validity and reliability testing, descriptive and inferential analysis, and interpretation of statistical results. A pre-post test design was employed using a 10-item Likert-scale instrument aligned with the workshop sessions. The Wilcoxon Signed-Rank Test was used due to non-normal pre-test score distribution. Results revealed a statistically significant improvement in student competency (W = 80.500, p < 0.001), with a large effect size (Cohen's d = 1.110) and a mean Normalized Gain of 35.4% (moderate category). Workshop evaluation scores were consistently high across all dimensions (M = 3.94–4.15 out of 5). These findings indicate that a structured, application-based workshop using accessible tools effectively improves students' quantitative research competency for academic writing.